Individualism in Everyday Communication among University Students: A Qualitative Study of Self-Expression and Social Interaction - Amaliyah, Ilmi (Forum Akademisi dan Dosen Peneliti (FAST), 2026)
This study investigates how individualism is enacted in the everyday communication of university students, examining self-expression, autonomy, and social interaction within both face-to-face and digital contexts. While prior research has predominantly treated individualism as a stable cultural or psychological trait, this study reconceptualizes it as a dynamic, interactionally accomplished, and contextually negotiated phenomenon. Employing a qualitative interpretive design, data were collected through semi-structured interviews, focused participant observations, and digital communication artifacts from fifteen purposively sampled undergraduate students. Data were analyzed using an iterative thematic approach informed by practice-based and power-sensitive perspectives, ensuring credibility through method triangulation, member reflection, and reflexive memoing. Findings reveal that students strategically deploy autonomy, assertiveness, and self-expression, modulating their communicative behavior according to relational considerations, institutional norms, and digital affordances. Individualism is neither absolute nor unbounded; rather, it is hybrid and relationally regulated, coexisting with concern for social harmony. Digital platforms extend opportunities for self-expression, yet visibility and audience awareness impose new constraints, illustrating that individualistic communication is always situated and mediated. The study contributes theoretically by advancing a practice-centered framework of individualism that foregrounds interactional accomplishment, contextual contingency, and structural constraint. Practically, it highlights the need for higher education institutions to recognize diverse forms of student engagement, including reflective silence, selective participation, and digitally mediated expression, as legitimate modes of agency. By reframing individualism as a communicative practice, this study provides both a robust theoretical lens and actionable insights for fostering balanced and contextually aware communication in higher education settings.